(3GdefGgL aj GdJQHjI GdQjGVjI s - (3RjO YHO Gddg(B, (3eMeO s ((3YeGf (B:s (3OGQ GdMGeO(B,s, 2019)
(3JMOK GdcJGH Yf GdJWhQ GdJGQjNj ddefGgL aj GdJQHjI GdQjGVjI , cPdc JNWjW h JUeje GdefGgL eGgjJg h GfhGYg h GdYhGed GdDKQI ajg , GjVG JfGhd CfhGY GdefGgL h NWhGJ hVYg h CNjQG YfGUQ GdefgL GdJQHhj h h GdGSS GdJj Jbhe YdjgG GdGfTWI h GfeGW GdJYdje h GdUYhHGJ Gdj JhGLg JWhQ GdefGgL (B.s
(3HjHdjhZQGajG U(B.283-295s
Keywords: (3GdJQHjI GdHOfjIs; (3GdJQHjI GdHOfjI(B:(3efGgLs